2019
DOI: 10.1080/19768354.2019.1661282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eicosapentaenoic acid and docosahexaenoic acid on C2C12 cell adipogenesis and inhibition of myotube formation

Abstract: Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) modulate cellular metabolic functions and gene expression. This study investigated the impacts of EPA and DHA on gene expression and morphological changes during adipogenic inducement in C2C12 myoblasts. Cells were cultured and treated with differentiation medium with and without 50 μM EPA and DHA. Cells treated with fatty acids had noticeable lipid droplets, but no formation of myotubes compared to control group cells. The expression levels of key gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
2
12
1
Order By: Relevance
“…Our finding that n-3PUFA (i.e., EPA) inhibits myogenesis is in agreement with accumulating evidence showing the negative effect of n-3PUFA on myotube formation in-vitro [17,19,22]. These studies highlight the potential negative effects of n-3PUFA consumption during pregnancy when de novo myogenesis is initiated at the embryonic and neonatal stages because disruption to myogenesis at this time may lead to postnatal muscle deficiencies in mass and function [50].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding that n-3PUFA (i.e., EPA) inhibits myogenesis is in agreement with accumulating evidence showing the negative effect of n-3PUFA on myotube formation in-vitro [17,19,22]. These studies highlight the potential negative effects of n-3PUFA consumption during pregnancy when de novo myogenesis is initiated at the embryonic and neonatal stages because disruption to myogenesis at this time may lead to postnatal muscle deficiencies in mass and function [50].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to our original research hypothesis, cotreatment of E2 and n-3PUFA did not have a synergistic effect on in-vitro myogenesis, raising the possibility that dietary supplements of fish oil (i.e., n-3PUFA) may interfere with the positive affect estrogen has on muscle regeneration in women on HRT. Recently, Ghnaimawi et al [17] showed that treatment of differentiating C2C12 myoblasts with 50 µM EPA and DHA for four days increased adipogenesis and inflammatory-related genes and reduced tube formation. We did not examine adipose cell formation in our cultures following treatment with EPA, but were able to identify that IL6 and adipose tissue related genes were uniquely expressed in cells treated with EPA (Tables S3 and S4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Very long-chain 3-oxoacyl-CoA reductase (Hsd17b12) catalyzes the second of the four reactions of the long-chain fatty acids elongation cycle, and this enzyme has 3-ketoacyl-CoA reductase activity, reducing 3-ketoacyl-CoA to 3-hydroxyacyl-CoA, within each cycle of fatty acid elongation. It may participate in the production of PUFAs of different chain lengths that are involved in multiple biological processes as precursors of membrane lipids and lipid mediators 34 , especially like EPA, which may potentially drive myoblasts to enter the quiescent state and enable adipogenic trans-differentiation of the myoblasts and impairs brown adipogenesis and thermogenic capacity 35,36 .…”
Section: Discussionmentioning
confidence: 99%